Effectiveness of Peer Tutoring Programs on Academic Performance in Middle School Mathematics - Muitange, Geoffrey (American Journal of Education and Practice, 2024)
Purpose: The aim of the study was to assess the effectiveness of peer tutoring programs on academic performance in middle school mathematics. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study found that such programs, where students tutor each other under structured guidance, contribute positively to learning outcomes. By fostering peer interaction and collaborative learning, these programs not only improve understanding of mathematical concepts but also boost confidence among students. Studies have highlighted significant improvements in grades and test scores among participants, suggesting that peer tutoring effectively supplements traditional classroom instruction. Moreover, the personalized attention received in these sessions helps to address individual learning gaps and reinforces key mathematical skills. Overall, the evidence underscores the effectiveness of peer tutoring programs in middle school mathematics, emphasizing their role in supporting academic achievement and student engagement in the subject. Implications to Theory, Practice and Policy: Social learning theory, zone of proximal development and self-determination theory may be used to anchor future studies on assessing the effectiveness of peer tutoring programs on academic performance in middle school mathematics. A key recommendation for enhancing the practice of peer tutoring programs in middle school mathematics is to encourage structured implementation that incorporates clear guidelines, goal-setting, and continuous monitoring and evaluation mechanisms. Advocating for policy initiatives that promote the integration of peer tutoring programs as a recognized and supported educational strategy within middle school mathematics curricula is crucial.